2004
DOI: 10.1111/j.0026-7902.2004.t01-15-.x
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Acquisition as Situated Practice: Task Accomplishment in the French Second Language Classroom

Abstract: This article provides an empirically based perspective on the contribution of conversation analysis (CA) and sociocultural theory to our understanding of learners' second language (L2) practices within what we call a strong socio-interactionist perspective. It explores the interactive (re)configuration of tasks in French second language classrooms. Stressing that learning is situated in learners' social, and therefore profoundly interactional, practices, we investigate how tasks are not only accomplished but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(79 citation statements)
references
References 35 publications
1
69
0
9
Order By: Relevance
“…He, 2004;Markee & Kasper, 2004;Mondada & Pekarek, 2004;Kasper, 2006;Pekarek Doehler, 2010;Barraja-Rohan, 2011;Seedhouse, 2013; and more recently CA has begun to be applied in online language learning environments (González-Lloret, 2015). González-Lloret points out that this is a growing area of research, an assertion that is supported by the number of studies in online learning environments that depart from a CA perspective (cf.…”
Section: Methodsmentioning
confidence: 99%
“…He, 2004;Markee & Kasper, 2004;Mondada & Pekarek, 2004;Kasper, 2006;Pekarek Doehler, 2010;Barraja-Rohan, 2011;Seedhouse, 2013; and more recently CA has begun to be applied in online language learning environments (González-Lloret, 2015). González-Lloret points out that this is a growing area of research, an assertion that is supported by the number of studies in online learning environments that depart from a CA perspective (cf.…”
Section: Methodsmentioning
confidence: 99%
“…Interactionally oriented language learning studies have begun to show how language learning in a social setting is emergent and co-constructed by its participants (Mondada & Pekarek-Doehler, 2004). In second language classrooms, objects of learning have been shown to be contingent upon interaction (Lee, 2010) and practiced through coordinated sense making processes in the interactional organization of talk.…”
Section: Interactive Learnables and Their Sourcesmentioning
confidence: 99%
“…During the last decade or so a more dialogical and action-based approach has begun to emerge within studies of pedagogical activities (Egbert, Niebecker, & Rezzara, 2004;Koschmann, Le Baron, Goodwin, & Feltovich, 2010;Koshik, 2002;Mondada & Pekarek-Doehler, 2004;Young & Miller, 2004). The significance of interaction, the in situ development of learners' productivity, and attention to different resources at the time of social interaction have steered research in this area toward the endogenous analysis of pedagogical activities (see Firth & Wagner, 2007).…”
Section: Toward the Study Of Learnablesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [2], the IRF routine was successfully applied and replicated in informal peer-to-peer foreign language interactions. Vaish employed IRF exchanges in English courses at elementary and junior high schools [3], while Mondada and Doehler taught children aged 10-12 years old French as a second language with the IRF sequence in Switzerland [4]. Although effective language interaction through IRF dialogue can improve student understand-ing, and language teachers can correct language errors by providing feedback, teachers must contend with heterogeneous language ability levels of students and limited class time, which are the main challenges encountered when teaching [5]; Pauli also found that teachers often ask new questions or offer further explanations without explicitly reviewing the answer or statement of the student [6].…”
Section: Introductionmentioning
confidence: 99%